OʻQUVCHILARNING INTERFAOL O’QITISH METODLARI VA TEXNOLOGIYALARI ASOSIDA KREATIVLIK QOBILYATLARINI RIVOJLANTIRISHI - Isfandiyorova Aziza (Лучшие интеллектуальные исследования, 2023)
Annotation: In the article, there is a scientific-practical discussion of the harmony of educational and physiological processes related to the reading activity of students in the primary school period, and the issues of proper development of the child’s perception in this process. Information provided.